(Cucumis ( تأثير ملوحة مياه الري في بعض الخصائص الفسلجية لصنفين من نبات الخيار sativus L.: A study the effect water salinity in some physiological properties for two species of cucumber plant (Cucumis sativus L.) - العبادي, عبد الوهاب ريسان (University of Thi-Qar Journal of Science, 2014)
A study was conducted on the effect of irrigated saline water in some physiological properties for two species of cucumber plant (Cucumis sativus L.). This study was included the effect of salinity concentrations (3, 6, 9 and 12 ) dS / m of salt solution of (NaCl) , in addition of distill water as a control on the carbohydrates , plant pigments (chlorophyll and carotene ) and percentages of water content and dry matter in shoot system of two plant species .The results of study were shaved , that , the increase of salinity concentrations causes an increase on the concentrations of carbohydrates and decreases on the concentrations of plant pigments ( chlorophyll A and B and total chlorophyll and carotenes) and the percentages of water content and dry matter in the shoot system of the two plant species and it was found a significant differences between them .